Geopolitics and expertise : knowledge and authority in European diplomacy - Kuus, Merje (RGS-IBG book series., 2013)
Geopolitics and Expertise is an in-depth exploration of how expert knowledge is created and exercised in the external relations machinery of the European Union. Provides a rare, full-length work on transnational diplomatic practice. Based on a rigorous and empirical study, involving over 100 interviews with policy professionals over seven years. Focuses on the qualitative and contextual, rather than the quantitative and uniform. Moves beyond traditional political science to blend human geography, international relations, anthropology, and sociology.